Evaluation of the Implementation of the Complete Systematic Land Registration Program (PTSL) in Increasing Legal Certainty of Land Ownership in Buol Regency - Syamsiar i. Mahmud; Rusli Dunggio; Nurbaya Nurbaya (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the implementation of the Complete Systematic Land Registration Program (PTSL) in an effort to improve legal certainty of land ownership in Buol Regency. The PTSL program is a national strategy designed to accelerate the land registration process comprehensively so that communities can obtain valid and legally binding land certificates. This study used a descriptive qualitative approach, involving Buol Regency Land Office employees, village officials, and community beneficiaries as research subjects. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model through data reduction, data presentation, and conclusion drawing. Data validity was strengthened through triangulation of sources and techniques. The results indicate that the PTSL implementation in Buol Regency is relatively effective. This is evident in the certification of 35,600 land plots, or approximately 89% of the total target of 40,000 plots. This program has been proven to increase legal certainty of land ownership, reduce land disputes by 70%, accelerate the certification process, and reduce costs for the community. Approximately 35% of the community has also used land certificates as collateral for loans for productive economic activities. Several factors supporting the success of PTSL include government support, high community participation, and strong coordination between agencies. However, program implementation still faces challenges such as limited human resources, a lack of measuring tools, and low digitization of land data. Overall, PTSL has succeeded in improving legal certainty and public welfare, but it still requires human resource capacity building, accelerated digitalization, and ongoing outreach to optimize the program in the future.